Available Approaches to Combining Traditional and Modern Medicine in China - Haiyan, Wang (Journal of Intellectual Disability - Diagnosis and Treatment, 2019)
The search for the best possible form of interaction between modern and traditional medicine in China is quite a controversial issue. It is established that there is a number of social and philosophical viewpoints concerning the problem of integration of modern and traditional medicine, including the following: their integration is impossible; Chinese and modern medicine can be combined in terms of mutual complementation in treatment practice; the integration is quite likely. The author proves that an important prerequisite for the solution to this problem is understanding of the role of the worldview factor and traditions of the Chinese population. The search for the ways to integrate traditional and modern medicine is possible only provided that there is necessary political support from the state.